Eksistensi Putusan Mahkamah Konstitusi - Fatriansyah, Fatriansyah (Universitas Batanghari Jambi, 2023)
The Constitution has stipulated that the Indonesian state is a state of law, the implementation of which is carried out by the government in accordance with the mandate in the 4th paragraph of the preamble to the 1945 Constitution of the Republic of Indonesia that its duty is to protect the entire Indonesian nation and all of Indonesia's blood as an embodiment of the 5th principle